Evaluation of Social Assistance in Reducing Income Inequality: Analysis of Poor Households in Indonesia - Rayhana Putri Roup (LifeSciFi, 2026)
This study evaluates the effectiveness of social assistance programs in reducing income inequality among poor households in Indonesia by shifting the focus from aggregate indicators to a micro-level household analysis. Using secondary data from the 2023–2025 National Socioeconomic Survey (Susenas) and the 2025 Integrated Social Welfare Data (DTKS), this study compares economic conditions between recipient and non-recipient households. The analysis employs descriptive statistics, Propensity Score Matching, and regression techniques to assess differences in consumption patterns, education participation, and access to health services. The results indicate that social assistance plays a significant role in stabilizing food consumption and improving access to basic education and healthcare among poor households. However, its impact remains largely short-term and consumptive, with limited effects on non-food consumption, productive investment, and long-term income improvement. Persistent issues such as mistargeting, limited benefit size, and weak integration with productive programs reduce the redistributive potential of social assistance in addressing income inequality. The study concludes that social assistance functions primarily as a social safety net rather than an instrument of economic mobility, highlighting the need for more integrated and household-based policy designs to achieve sustainable inequality reduction.